Order in multi-attribute product choice decisions: Evidence from~discrete~choice experiments combined with eye tracking - Nick Zuschke (Journal of Behavioral Decision Making, 2023)
Over time, research on order effects during information searching and choice tasks has received thorough attention in marketing, psychology, and economics. When early information search influences choice in favor of that information, it is called primacy; the equivalent for later information search is called recency. However, research that disentangles primacy and recency effects during multi-attribute product choice, as well as studies on the cognitive processes underlying primacy and recency effects are lacking. I address this gap with two choice-based conjoint experiments combined with eye tracking and by means of multilevel mediation analysis. Consistent with my prediction that to counterbalance the impact of decision irrelevant information on choice through early information search by later information search is mentally too costly, I find that “spatial position” biases choice due to primacy rather than recency. This bias, however, is small. This suggests that for decision irrelevant information, the causal influence of attention on choice generalizes to more complex decisions, though with little impact. Consistent with my prediction that the level of information elaboration moderates the mediation process, increasing task motivation decreases the dominance of primacy.
Keywords: 650; bounded rationality; conjoint; consumer decision-making; eye tracking; multi-attribute; order; primacy; recency